2007
DOI: 10.2337/db06-0717
|View full text |Cite
|
Sign up to set email alerts
|

Role of Excess Glycogenolysis in Fasting Hyperglycemia Among Pre-Diabetic and Diabetic Zucker (fa/fa) Rats

Abstract: Sources of plasma glucose and glucose turnover were investigated in 8-week-old (pre-diabetic) and 13-week-old (diabetic) Zucker (fa/fa) rats after a 24-h fast. Intraperitoneal 2 H 2 O was administered and [3,4-13 C 2 ]glucose and [U-13 C 3 ]propionate were infused into conscious active rats. 13 C nuclear magnetic resonance analysis of monoacetone glucose derived from blood glucose indicated that glucose production was increased significantly in 8-and 13-weekold fa/fa rats compared with age-matched Zucker (؉/؉)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 35 publications
5
22
0
Order By: Relevance
“…These data suggest that the hepatic TCA cycle is significantly more active in obese postprandial cats, but pyruvate cycling appears to modulate gluconeogenesis and EGP. A regulatory role for pyruvate cycling has also been described in Zucker (fa/fa) rats (34). We have previously shown that fasted female obese cats had similar changes, including higher pyruvate cycling (41).…”
Section: Discussionmentioning
confidence: 91%
“…These data suggest that the hepatic TCA cycle is significantly more active in obese postprandial cats, but pyruvate cycling appears to modulate gluconeogenesis and EGP. A regulatory role for pyruvate cycling has also been described in Zucker (fa/fa) rats (34). We have previously shown that fasted female obese cats had similar changes, including higher pyruvate cycling (41).…”
Section: Discussionmentioning
confidence: 91%
“…Very low rates of glycogenolysis have been reported in one rat strain fasting for 24 h, but in obese rats (fa/fa) hepatic glycogen was maintained and contributed 10 -15% of EGP (35). We did not measure hepatic glycogen concentration, but it seems that glycogen stores were depleted early in fasting.…”
Section: Discussionmentioning
confidence: 99%
“…If skeletal muscle resembles heart, where this discrepancy is broadly independent of ATP turnover (32) (in effect, a constant error), the 20 -40% P i /ATP exchange defect in HF (21a) and other IR states (4,28,29,36) presumably underestimates that in ATP synthesis. However, the similar percent defects in P i /ATP exchange and tricarboxylic cycle (TCAC) flux measured by 13 C MRS in IR (4,28,29) suggest that the discrepancy is turnover dependent (a proportional error). This is not resolved by the observations that triiodothyronine (14,22) and 2,4-dinitrophenol (14) decrease, whereas uncoupling protein-3 knockout increases (8), the ratio of P i /ATP exchange to TCAC flux [a qualitative index of coupling (15,16)] or that 2,4-dinitrophenol does not affect directly measured glycolytic exchange (14).…”
Section: Absolute Ratesmentioning
confidence: 99%
“…Assumptions: P:O ϭ 2.16 from mouse ischemic 31 P MRS/NIRS (shown as linked points) (24,25); human leg muscle mass ϭ 10 kg; V O2/TCAC flux ϭ 3, and 1 mol O2 ϭ 25.5 l (10); wet/dry ϭ 4.35, and cell water ϭ 0.67 l/kg (7). Dashed lines give overall means of published values, for which rat/human ratio is ϳ3:5 by V O2 and 13 C MRS (cf expected ϳ4) and mouse/human ratio is ϳ4:7 by ischemic 31 P MRS/NIRS and 13 C MRS (cf expected ϳ7); Pi/ATP exchange is similar in human and rat (21a) but lower in the single mouse study (8). B: rates in rat muscle vs. PCr concentration ([PCr]) relative to resting values.…”
Section: Flux Vs Capacity Supply Vs Demandmentioning
confidence: 99%
See 1 more Smart Citation